2019
DOI: 10.1016/j.pmrj.2018.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Dextromethorphan/Quinidine for Pseudobulbar Affect Following Stroke: Safety and Effectiveness in the PRISM II Trial

Abstract: DM/Q effectively treated PBA and was associated with global and functional improvement; adverse events were consistent with the known safety profile of DM/Q.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
(49 reference statements)
0
2
0
1
Order By: Relevance
“…All the study participants received DM/Q, 20/10 mg twice daily. Studies have evaluated fluoxetine, paroxetine, and citalopram trials in stroke patients with pseudobulbar affect with reduced severity and episode rates [10]. However, in the PRISM II trials, the dextromethorphan/quinidine medication showed improvement in the different efficacy scales that were used, including Neurologic Study-Lability Scale (CNS-LS) as primary efficacy measures, and the Clinical and Patient/Caregiver Global Impression of Change (CGI-C and PGI-C), Quality of Life-Visual Analog Scale (QOL-VAS), Patient Health Questionnaire (PHQ-9), and the Mini-Mental State Examination (MMSE).…”
Section: Discussionmentioning
confidence: 99%
“…All the study participants received DM/Q, 20/10 mg twice daily. Studies have evaluated fluoxetine, paroxetine, and citalopram trials in stroke patients with pseudobulbar affect with reduced severity and episode rates [10]. However, in the PRISM II trials, the dextromethorphan/quinidine medication showed improvement in the different efficacy scales that were used, including Neurologic Study-Lability Scale (CNS-LS) as primary efficacy measures, and the Clinical and Patient/Caregiver Global Impression of Change (CGI-C and PGI-C), Quality of Life-Visual Analog Scale (QOL-VAS), Patient Health Questionnaire (PHQ-9), and the Mini-Mental State Examination (MMSE).…”
Section: Discussionmentioning
confidence: 99%
“…The drug combination had a favorable safety profile, the most common adverse events being diarrhea and dizziness. 99,100 The administration of dextromethorphan /quinidine with antidepressants, serotonergic drugs and MAO inhibitors is contraindicated, because of the risk of dangerous interactions, in particular serotonergic syndrome.…”
Section: Managementmentioning
confidence: 99%
“…En Europa obtuvo autorización por la Agencia Europea de Medicamentos en 2013, pero fue retirado de mercado en 2016 por decisión de la empresa farmacéutica a cargo. El dextrometorfano actúa sobre los Alet, M.; Segamarchi, C.; Claverie, S.; González, L.; Lepera, S.; Rey, R. receptores sigma-1 y NMDA en el cerebro, y el sulfato de quinidina permite que el dextrometorfano alcance concentraciones terapéuticas (11). Hemos utilizado este tratamiento en el paciente con ACV crónico y SPB (sin depresión), con modestos beneficios a los seis meses de seguimiento.…”
Section: Placs Negativaunclassified